2.6 W diode-pumped actively mode-locked Tm:YLF laser. (13th February 2015) - Mužík, J; Jelínek, M; Vyhlídal, D; Kubeček, V
Abstract: We have experimentally demonstrated an actively mode-locked laser with a Tm 3+ -doped yttrium lithium fluoride crystal (YLF). A continuous mode-locked regime was achieved using an acousto-optic modulator and a stable train of pulses with 149.3 MHz repetition rate, 170 ps pulse width and 2.6 W average output power at 1.91  µ m in a nearly diffraction-limited beam was obtained. To the best of our knowledge, this is the first report on a diode-pumped actively mode-locked bulk thulium laser with a stable output.